Chapter La riforma delle risorse proprie e la possibile introduzione di un tributo europeo - Traversa, Edoardo (Studi e saggi, 2022)
In the European Union, negotiations on the financial perspectives and the determination of the Union's own resources focus mainly on the amount of the individual states' contributions, and much less on the Union's fiscal competence. This weakens the Union's ability to conduct ambitious long-term policies, potentially mortgaging its very raison d'être. Recent developments related to the COVID-19 crisis (and beyond) seem to open a window for future changes. The European tax is an issue that provokes a wide debate at both the European and national levels, and not only of a political nature, between sovereignists and federalists, but also on the technical-legal-constitutional modalities that such a change would imply. For this reason, it is useful to present a structured analysis first of the financial instruments assigned to the EU, then of a reform of own resources and, finally, of the possibility of envisaging the birth of a European tax, albeit with an awareness of the limits of such a reform with regard to the current constitutional set-up of the European Union. Consequently, it will also be necessary to ask what kind of tax would be appropriate for this purpose.